Effect of Cr content on microstructure and abrasive wear behaviour of Co-based alloys - Somunkiran, I.; Nursoy, M.; Celik, H. (Sage Publications Inc, 2011)
In this study, a series of Co-Cr-Mo alloys with varying Cr contents were produced by powder metallurgy technique, and the effects of Cr content on microstructure and abrasive wear behaviour were studied. Seven different powder compositions having 15-35 wt-%Cr were used in the experiments. Homogeneously blended powders were cold compacted in a 120 kN single action press. The sintering process was carried out at 1200 degrees C for 60 min in an argon atmosphere. The effects of Cr on the microstructure and abrasion wear performance of the produced powder metallurgy alloys were investigated using SEM, energy dispersive spectroscopy and abrasion wear tests. Abrasive wear resistances were observed to have been increasing up to 27.5 wt-%Cr addition and decreasing subsequently.
Keywords: Cobalt-based alloys; Powder metallurgy; Wear